The Effect of Health Education with Booklet Media on The Knowledge and Attitude of Female Students in Performing SADARI (Breast Self-examination) at Kuripan Highschool - Emilyani, Desty; Arip, Moh; Jafar, Sitti Rusdianah; Afriani, Fia (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2024)
Breast cancer is a disease in which cells lose their normal control mechanisms resulting in abnormal, rapid, and uncontrolled growth of breast tissue. One of the factors causing the high incidence of breast cancer is the lack of early detection education provided to adolescents. Consequently, knowledge and attitude of adolescents in conducting Self Breast Examination (SADARI) as an early detection of breast cancer is still lacking. In fact, there are still many adolescents who are unable to perform SADARI because they do not know how to do SADARI. Purpose of the studyto determine the effect of health education with booklet on the knowledge and attitudes of female adolescents in conducting SADARI at Kuripan Highschool. This research uses pre-experimental research design using one group pre-posttest with 65 female students as the respondents. The sampling technique used in this study was proportional stratified random sampling. The data consisted of primary and secondary data collected through interviews and questionnaires. The data processing technique used a Non-Parametric test, namely the Wilcoxon Sign Rank Test. The results showed thatbefore given health education, most respondents had poor knowledge (36; 56%) and had a negative attitude (36 ; 55%). After given health education, all respondents were included in good knowledge (65;100%) and had a positive attitude (37;57%). It can be concluded that there is an influence of health education using booklet on the knowledge and attitudes of female adolescents in doing SADARI (Breast Self-Examination) at Kuripan Highschool